Team-Based Care: Quality and Process Improvement At Närhälsan Olskroken - Olaniyi, Omolara Ramota (My University, 2026)
Primary care in Sweden faces a structural tension between growing patient demand and persistent physician shortages. At Närhälsan Olskroken, a centrally located primary care center in Gothenburg serving approximately 14,306 listed patients, the longstanding reliance on an individual Patient-Responsible Doctor (Patientansvarig läkare, PAL) model has produced fragmented care pathways, low care continuity, and a high burden of isolated clinical decisionmaking, particularly during mandatory six-month ST doctor hospital rotations. Three high-need patient groups, patients aged 80 and above, patients on long-term sick leave exceeding two months, and frequent visitors with four or more annual contacts, bear an unequal share of these continuity failures. This thesis employs a research methodology integrated with the DMAICL (Define, Measure, Analyze, Improve, Control, and Learn) and PDCA (Plan, Do, Check, and Act) quality improvement frameworks to design and initiate a phased transition from the individual patientresponsible doctor model to a cross-functional, team-based care model. Data were collected from the Asynja electronic health record system and the Telia Ace telephony platform, a staff pulse survey, semi-structured interviews with the chiefs of staff of two external Närhälsan facilities, and naturalistic workflow observation. The baseline dataset identified 517 patients aged 80 and above, 177 patients on extended sick leave, and 363 frequent visitors, with contact frequency ranging from five to twenty-two annual visits. The findings identify three interdependent structural prerequisites for a successful transition: the administrative integration of the currently siloed rehabilitation division into cross-professional clinical rounds, the reconfiguration of the Telia Ace telephony system to route incoming calls by birthdate to designated team nurses, and the standardization of follow-up documentation within Asynja to eliminate non-resilient, informal physician workarounds. Comparative interview evidence from a mature three-year team-based implementation confirms that birth-date telephony routing significantly reduces re-contact rates and wait times, while a generalized queue structure as currently used at Olskroken yields no measurable improvement in these indicators. The proposed model centers on four cross-functional care teams, each composed of specialist physicians, ST doctors, nurses, and rehabilitation professionals, serving birth-date-allocated patient lists. Weekly interprofessional meetings to discuss the status of patients undergoing medical checkups or treatment are being proposed to replace the current unstructured administrative meeting and form the operational core of the coordination mechanism. Although the Phase 1 pilot was ongoing at the time of writing and full longitudinal outcome data were not yet available, the study concludes that the integration of structured team-based workflows, targeted telephony routing, and standardized EHR documentation constitutes a viable and theoretically grounded response to both Olskroken's specific operational vulnerabilities and the broader national challenge of delivering sustainable, equitable primary care under conditions of constrained physician supply.
Keywords: Team-based care; Interprofessional collaboration; Primary care; Lean management; DMAICL; PDCA; Care continuity; Swedish healthcare; Närhälsanprocess improvement